Mac OS X Snow Leopard visual quick tips - Sheppard, Rob (Visual read less, learn more., 2009)
Demonstrates the operating system's features, customizing the desktop, managing files and folders, working with data, using multimedia, accessing the Internet, and printing and using graphics.